2016
DOI: 10.5152/tao.2016.1700
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fine-Needle Aspiration Biopsy in the Management of Salivary Gland Masses

Abstract: Objective: Fine-needle aspiration biopsy (FNAB) is widely used in the management of salivary gland masses. Its main advantage is its ability to differentiate benign from malignant disease. In this study, we aimed to evaluate the diagnostic ability of FNAB in salivary gland masses. Methods:The records of patients who had undergone FNAB before parotidectomy or submandibular gland excision between 2005 and 2013 were retrospectively analyzed. FNAB results were classified as negative, positive, suspicious for malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
0
18
2
1
Order By: Relevance
“…Pleomorphic adenoma accounted for 47% of benign tumors, while Warthin tumor accounted for 37% of them. In previous studies, pleomorphic adenoma has been reported to be the most common benign tumor in all salivary glands [5][6][7][8][9][10][11][12][13][14][15][16][17]. However, in our study, Warthin tumor was detected in the parotid gland more than pleomorphic adenoma, unlike the literature.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Pleomorphic adenoma accounted for 47% of benign tumors, while Warthin tumor accounted for 37% of them. In previous studies, pleomorphic adenoma has been reported to be the most common benign tumor in all salivary glands [5][6][7][8][9][10][11][12][13][14][15][16][17]. However, in our study, Warthin tumor was detected in the parotid gland more than pleomorphic adenoma, unlike the literature.…”
Section: Discussioncontrasting
confidence: 81%
“…However, in our study, Warthin tumor was detected in the parotid gland more than pleomorphic adenoma, unlike the literature. In addition, among all salivary gland tumors, Warthin tumor rate was reported as between 6% and 21% in large series of studies conducted in different regions of the world [5][6][7][8][9][10][11][12][13][14][15][16], while it was found as 26.2% in our study. In the light of this information, it can be said that Warthin tumor is more frequently seen in our region compared to many parts of the world.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Accurate detection of malignancies at an early stage will not only ameliorate the survival rate but also contribute significantly to the quality of the patient's life. Currently, Biomedical Imaging techniques such as Computed Tomography (CT), Magnetic Resonance Imaging (MRI) and pathological fine-needle aspiration biopsy are being used for detection of cancer [ 358 , 359 ]. However, aspiration tissue biopsy is invasive and can cause bleeding, squamous metaplasia, fibrosis, and necrosis during collection [ 360 ].…”
Section: Sevs In Cancer Liquid Biopsymentioning
confidence: 99%